109k views
4 votes
2) Use the elimination method to solve for x and y.

equation 1: -x/3 - y/6 = -4
equation 2: -x/6 + y/2 = -9

solve for y _____
solve for x _____

User TheUser
by
5.4k points

2 Answers

7 votes

Answer:

1: 2x + y = 24

2: x - 3y = 54

Explanation:

User JCLL
by
5.5k points
3 votes

Answer:


y = - 3. \\ x = - 13.5

Explanation:


equation 1: -x/3 - y/6 = -4 \: \: = - (x)/(3) - (y)/(6) = - 4 \\ \\ </p><p>equation 2: -x/6 + y/2 = -9 \: \: = - (x)/(6) + (y)/(2) = - 9 \\ \\ - (x)/(3) - (y)/(6) = - 4 \\ - 6x - 3y = - 72 ...(eq3.) \\ \\ - (x)/(6) + (y)/(2) = - 9 \\ - 2x + 6y = - 9...(eq4.) \\ \\ \\ 2 * - 6x - 3y = - 72 ...(eq3.) = > - 6y = -1 44 \\6 * - 2x + 6y = - 9...(eq4.)= > - 36y = -54 \\ - 6y - ( - 36y) = - 144 - ( - 54) \\ 30y = - 90 \\ y = - (90)/(30) \\ y = - 3. \\ x = - 13.5</p><p>

User Vlad Shevchenko
by
4.8k points